A unique role of flagellar function in Aliivibrio salmonicida pathogenicity not related to bacterial motility in aquatic environments. (August 2017) - Nørstebø, Simen Foyn; Paulshus, Erik; Bjelland, Ane Mohn; Sørum, Henning
Abstract: Aliivibrio salmonicida is the causative agent of cold-water vibriosis, a septicemia of farmed salmonid fish. The mechanisms of disease are not well described, and few virulence factors have been identified. However, a requirement for motility in the pathogenesis has been reported. Al. salmonicida is motile by the means of lophotrichous polar flagella, consisting of multiple flagellin subunits that are expressed simultaneously. Here we show that flagellin subunit FlaA, but not FlaD, is of major importance for motility in Al. salmonicida . Deletion of flaA resulted in 62% reduction in motility, as well as a reduction in the fraction of flagellated cells and number of flagella per cell. Similarly, deletion of the gene encoding motor protein motA gave rise to an aflagellate phenotype and cessation of motility. Surprisingly, we found that Al. salmonicida does not require motility for invasion of Atlantic salmon. Nevertheless, in-frame deletion mutants defective of motA and flaA were less virulent in Atlantic salmon challenged by immersion, whereas an effect on virulence after i.p. challenge was only seen for the latter. Our results indicate a complex requirement for motility and/or flagellation in the pathogenesis of cold-water vibriosis, but the mechanisms involved remain unknown. We hypothesize that the differences in virulence observed after immersion and i.p. challenge are related to the immune response of the host. Highlights: Motility is not required for skin passage of Atlantic salmon. Flagellin subunit FlaA, but not FlaD, plays a key role in motility and virulence. Flagella are involved in virulence after immersion, but not after i.p. challenge.